Controlling Optical Bistability in a Five-level Cascade EIT Medium - Thuan, Phan Van; Anh, Ta Tram; Trung, Le Canh; Dung, Nguyen Tien; Nga, Luong Thi Yen; Khoa, Dinh Xuan; Doai, Le Van; Bang, Nguyen Huy; Ai, Nguyen Van (Communications in Physics, 2016)
Optical bistability (OB) of an electromagnetically induced transparency (EIT) medium placed in a conventional unidirectional ring cavity is investigated numerically. The medium is excited by a coupling and probe laser lights via a five-level cascade scheme. It is shown that optical bistabe states with controllable switching threshold intensities and width are established simultaneously in three spectral regions corresponding to EIT windows. The current numerical result is compared to a previous analytical result showing influence of coherence terms neglected in the analytical model.